Energy recovery behavior of low-frequency electric heating assisted depressurization in Class 1 hydrate deposits. (1st February 2022) - Zhao, Ermeng; Hou, Jian; Ji, Yunkai; Liu, Yongge; Bai, Yajie
Highlights: The gas recovery behaviors of Class 1 hydrate deposits under low-frequency electric heating assisted depressurization are studied. The contribution of hydrate layer to gas production is significantly enhanced under electric heating. Linear decreasing voltage mode exhibits better production performance than constant voltage mode. Electric heating for Class 1 hydrate deposits is feasible with high energy efficiency ratio. Abstract: Class 1 hydrate deposits are characterized by a free gas layer (FGL) underneath the hydrate-bearing layer (HBL) and are considered as the most potential target for commercial exploitation. To improve the contribution of hydrate decomposition to gas production, an efficient development method of low-frequency electric heating assisted depressurization under five-point well pattern is proposed for Class 1 hydrate deposits, which involves the implementation of electric heating after a certain period of depressurization. Based on the geological data of Messoyakha gas field, the numerical simulation model is established. Then the energy recovery behaviors under single depressurization and the proposed method are investigated through numerical simulation approach. Results indicate that the gas production rate of Class 1 hydrate deposits is extremely high at the initial stage of depressurization, but decreases sharply due to insufficient reservoir energy. After the implementation of electric heating, hydrate decomposition and gas production are significantly improved, and a considerable energy efficiency ratio is obtained. Under the same heat input, the linear decreasing voltage mode exhibits better production performance than the constant voltage mode, and can avoid the continuous high temperature near the wellbore to damage the electrode elements, which has greater potential for the exploitation of hydrate deposits. At the end of 10 years of production, a cylindrical hydrate decomposition zone with a radius of about 40 m is formed around each production well. The simulation results confirm the feasibility of the proposed method and provide new insights for enhancing gas recovery in Class 1 hydrate deposits.